Cost analysis of early discharge using combined copeptin/cardiac troponin testing versus serial cardiac troponin testing in patients with suspected acute coronary syndrome - Reinhold, Thomas; Giannitsis, Evangelos; Frankenstein, Lutz; Vafaie, Mehrshad (PLOS ONE, 2018)
Background Symptoms indicating acute coronary syndrome are commonly seen in emergency rooms, but only 10% of patients are actually diagnosed with acute myocardial infarction (AMI). The Guidelines for the diagnosis of patients with suspected AMI include either multiple testing of cardiac troponin (cTN) or a single combined test of cTN and copeptin, which facilitates earlier diagnosis or exclusion of AMI. The aim of the present analysis was to investigate the impact of combined copeptin/cTN testing on health care resource consumption and related costs both during and after initial hospital treatment. Methods and results The analysis was based on the BIC-8 trial and financial data of participating study sites. A cost analysis was carried out primarily from the hospital perspective and secondarily from the perspective of German statutory health insurers. The underlying assumptions of the investigation were tested for robustness in additional sensitivity analyses. In total, the data of 713 patients (n = 359 combined copeptin/cTN testing, n = 354 serial cTN testing) were evaluated. From a hospital perspective, the combined copeptin/cTN testing showed a reduced number of medical procedures and a lower frequency of inpatient admissions. The average staff time was significantly reduced by a mean of 49 minutes (95% confidence interval (CI) 46 to 53) per patient, accompanied by a significant mean reduction of 131 minutes (95%CI 104 to 158) in the time patients stayed in the emergency room. The initial hospital treatment was less cost-intensive. Over the entire study period, no significant cost differences were observed between the groups for health insurance. Conclusion The combined copeptin/cTN testing has the potential to save costs and staff time in acute care and for the entire hospital stay. The primary explanations for these findings are early identification and ruling out patients without AMI along with the associated reduced need for acute medical treatment. Trial registration ClinicalTrials.gov NCT01498731